Tri-axial shaking table testing of lighting support systems with pulley friction dampers and integrated dummy masses - Tran-Van Han; Sung Chan Kim; Jiuk Shin; Nguyen Huu Cuong; Kihak Lee (Results in Engineering, 2024)
Investigating pulley wireway systems equipped with friction dampers as alternatives to traditional exposed raceway light fixtures, this study adheres to the ICC-ES AC156 standard and evaluates the impact of system mass and connector types on seismic behavior using shaking table tests. The key findings indicate that an increased system mass variably affects the fundamental frequency of the system, depending on the type of connectors. In terms of earthquake performance, direct connectors outperformed pole connectors in the original system configuration, and the addition of dummy masses significantly reduced seismic energy while stabilizing acceleration responses in pole connector systems. Moreover, the study underscores the critical importance of minimizing pole length in systems using pole connectors and adopting a lower mounting height in systems with direct connectors to improve seismic performance.